Application of Plasmonic Metal Nanoparticles in TiO2-SiO2 Composite as an Efficient Solar-Activated Photocatalyst: A Review Paper - Joseph, Collin G.; Taufiq-Yap, Yun Hin; Musta, Baba; Sarjadi, Mohd Sani; Elilarasi, L. (Frontiers in Chemistry, 2021)
Over the last decade, interest in the utilization of solar energy for photocatalysis treatment processes has taken centre-stage. Researchers had focused on doping TiO2 with SiO2 to obtained an efficient degradation rate of various types of target pollutants both under UV and visible light irradiation. In order to further improve this degradation effect, some researchers resorted to incorporate plasmonic metal nanoparticles such as silver and gold into the combined TiO2-SiO2 to fully optimise the TiO2-SiO2’s potential in the visible light region. This article focuses on the challenges in utilizing TiO2 in visible region, how SiO2 helps in enhancing photocatalytic activity of TiO2-SiO2 and how plasmonic metal nanoparticles (Ag and Au) edges the TiO2-SiO2 into an efficient solar photocatalyst.